Pathobiology of Salmonella, Intestinal Microbiota, and the Host Innate Immune Response - Santos, Renato Lima (Frontiers in Immunology, 2014)
Salmonella is a relevant pathogen under a clinical and public health perspective. Therefore, there has been a significant scientific effort to learn about pathogenic determinants of this pathogen. The clinical relevance of the disease, associated with the molecular tools available to study Salmonella as well as suitable animal models for salmonellosis, have provided optimal conditions to drive the scientific community to generate a large expansion of our knowledge about the pathogenesis of Salmonella-induced enterocolitis that took place during the past two decades. This research effort has also generated a wealth of information on the host immune mechanisms that complements gaps in the fundamental research in this area. This review focus on how the interaction between Salmonella, the microbiota and intestinal innate immunity leads to disease manifestation. As a highly successful enteropathogen, Salmonella actively elicits a robust acute intestinal inflammatory response from the host, which could theoretically lead to the pathogen demise. However, Salmonella has evolved redundant molecular machineries that renders this pathogen highly adapted to the inflamed intestinal environment, in which Salmonella is capable of outcompete resident commensal organisms. The adaptation of Salmonella to the inflamed intestinal lumen associated with the massive inflammatory response that leads to diarrhea, generate perfect conditions for transmission of the pathogen. These conditions illustrate the complexity of the co-evolution and ecology of the pathogen, commensals and the host.